2020
DOI: 10.3390/catal10080854
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Binary MgO/SiO2 Mixed Oxide Catalysts for the Conversion of Ethanol to 1,3-Butadiene

Abstract: The demand for 1,3-butadiene, one of the most important raw materials in the rubber industry, is constantly increasing. The Lebedev process is a classical method of producing 1,3-butadiene from ethanol, which is to be optimized with regard to the mixed oxide catalysts used. In this work, the binary MgO/SiO2 solid system was tested with regard to its optimum chemical composition for the catalytic conversion of ethanol to 1,3-butadiene. Furthermore, novel mesoporous mixed oxides were prepared to investigate thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…1 The potential of heterogeneous catalytic ETB process has even been demonstrated at industrial level. 2 The most commonly used supports/catalysts for the reaction are mixed oxides, such as MgO-SiO 2 3,4,[13][14][15][16][17][18][19][20][21][22]5,[23][24][25][26][27][28][29][6][7][8][9][10][11][12] or ZrO 2 -SiO 2 [30][31][32][33][34] , and their derivatives, obtained through modification by metals, such as, Ag 4,27,31,35,36 , Cu 16,27,33 , and Au 10 , or by metal oxides ZrO 2 9,36,37 , ZnO 9,16,19,23,…”
Section: Introductionmentioning
confidence: 99%
“…1 The potential of heterogeneous catalytic ETB process has even been demonstrated at industrial level. 2 The most commonly used supports/catalysts for the reaction are mixed oxides, such as MgO-SiO 2 3,4,[13][14][15][16][17][18][19][20][21][22]5,[23][24][25][26][27][28][29][6][7][8][9][10][11][12] or ZrO 2 -SiO 2 [30][31][32][33][34] , and their derivatives, obtained through modification by metals, such as, Ag 4,27,31,35,36 , Cu 16,27,33 , and Au 10 , or by metal oxides ZrO 2 9,36,37 , ZnO 9,16,19,23,…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of biomass energy such as lignin, cellulose, and hemicellulose, ethanol has been widely developed and adopted as a renewable energy resource. Many valuable chemical products have been made based on ethanol, especially 1,3-butadiene, proposed by Lebedev and Ostromislensky , to provide raw materials for downstream rubber products. , The mechanism of aldol condensation in the process of ethanol to 1,3-butadiene is well-accepted, consisting of the ethanol dehydrogenation, aldol condensation, Meerwein–Ponndorf–Verley (MPV) reaction, and dehydration reaction, where a multifunctional catalyst is needed for different reaction steps. , The surface of MgO catalyst has both acid and base properties, which makes MgO catalyst a versatile catalyst and profoundly impacts the process of ethanol to 1,3-butadiene as an effective component. ,, It is likely most difficult for the MPV reaction to understand the mechanism due to the presence of Lewis acid sites …”
Section: Introductionmentioning
confidence: 99%
“…4,5 The mechanism of aldol condensation in the process of ethanol to 1,3-butadiene is well-accepted, 6−9 consisting of the ethanol dehydrogenation, aldol condensation, Meerwein−Ponndorf− Verley (MPV) reaction, and dehydration reaction, where a multifunctional catalyst is needed for different reaction steps. 10,11 The surface of MgO catalyst has both acid and base properties, which makes MgO catalyst a versatile catalyst and profoundly impacts the process of ethanol to 1,3-butadiene as an effective component. 10,12,13 It is likely most difficult for the MPV reaction to understand the mechanism due to the presence of Lewis acid sites.…”
Section: Introductionmentioning
confidence: 99%
“…MgO-SiO 2 , which was reported as the best catalyst for butadiene formation from ethanol, [24][25][26] as well as MgO and SiO 2 , was selected as catalysts for ethanol to butadiene conversion and acetaldehyde condensation in this work. The characterization results showed that the prepared catalyst was consistent with previous reports, and the two components were dispersed well (Fig.…”
mentioning
confidence: 99%